Email
Chat with tutor
logo

Ask Questions, Get Answers

X
 
Answer
Comment
Share
Q)

Sum of m term of an AP is the same of its n term show that the sum of m+n t

Sum of m term of an AP is the same of its n term show that the sum of m+n terms is zero

1 Answer

Comment
A)
Sum of m terms=Sum of n terms

=> m/2 * (2a + (m-1)d) = n/2 * (2a + (n-1)d)
 Cancelling 2 in the denominator on both sides,

we get

m(2a + (m-1)d) - n(2a+ (n-1)d) = 0
 
 2am + m^2d - md -2an -n^2d +nd =0
 
 2a(m-n) + (m^2 - n^2)d -(m - n)d =0
 
 2a(m-n) + ( (m + n) (m- n) ) d - (m - n )d = 0
 
 Taking (m-n) common
 
 
 2a + ( m + n -1) d = 0 ------------ (1)
 
 
 S m+n = m+n/2( 2a + (m+n -1)d
 
 we know that 2a + (m+n)d is 0 from eqn. 1
 
 
 therefore S m+n = 0
Help Clay6 to be free
Clay6 needs your help to survive. We have roughly 7 lakh students visiting us monthly. We want to keep our services free and improve with prompt help and advanced solutions by adding more teachers and infrastructure.

A small donation from you will help us reach that goal faster. Talk to your parents, teachers and school and spread the word about clay6. You can pay online or send a cheque.

Thanks for your support.
Continue
Please choose your payment mode to continue
Home Ask Homework Questions
Your payment for is successful.
Continue
...